A-Posteriori Local Error Estimates of Boundary Element Methods with Some Pseudo-Differential Equations on Closed Curves (Journal of Computational Mathematics, 1992)
In this paper we show local error estimates for the Galerkin finite element method applied to strongly elliptic pseudo-differential equations on closed curves. In these local estimates the right hand sides are obtained as the sum of a local norm of the residual, which is computable, and additional terms of higher order with respect to the computable, and additional terms of higher order with respect to the meshwidth. Hence, asymptotically, here the residual is an error indicator which provides a corresponding self-adaptive boundary element method.